2008
DOI: 10.3104/reports.2005
|View full text |Cite
|
Sign up to set email alerts
|

Medical issues among children and teenagers with Down syndrome in Hong Kong

Abstract: We examined the prevalence of medical problems in children and teenagers with Down syndrome in Hong Kong. Methods: Children with Down syndrome receiving care from seven regional hospitals were included and their hospital records were reviewed. A total of 407 patients, aged between 0.06 and 17.16 years were included. Cardiovascular problems were observed in 216 (53%), endocrine problems in 111 (27%), gastrointestinal problems in 46 (11%), haematological problems in 18 (4%), neurological problems in 27 (7%), sle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 16 publications
1
24
1
Order By: Relevance
“…Compared with previously reported data on congenital malformations in liveborn DS (25,26), the incidence of congenital duodenal atresia was significantly higher among PCH patients with DS. Compared with the ECM data for the 1434 PCH patients without DS in the present study, the incidences of ventricular septal defect, atrial septal defect, patent ductus arteriosus, endocardial cushion defect, pulmonary hypertension, congenital atrioventricular block, annular pancreas, congenital duodenal atresia, anal atresia, and syndactyly of the hand (unknown) were significantly higher among the PCH patients with DS.…”
Section: Patient Characteristicscontrasting
confidence: 89%
See 1 more Smart Citation
“…Compared with previously reported data on congenital malformations in liveborn DS (25,26), the incidence of congenital duodenal atresia was significantly higher among PCH patients with DS. Compared with the ECM data for the 1434 PCH patients without DS in the present study, the incidences of ventricular septal defect, atrial septal defect, patent ductus arteriosus, endocardial cushion defect, pulmonary hypertension, congenital atrioventricular block, annular pancreas, congenital duodenal atresia, anal atresia, and syndactyly of the hand (unknown) were significantly higher among the PCH patients with DS.…”
Section: Patient Characteristicscontrasting
confidence: 89%
“…The observed number of ECMs (O) was compared to the expected number of ECMs (E) based on the data from the JAOG or previously reported data (23)(24)(25)(26)(27)(28) and the total number of patients. Consequently, the 95% CI was calculated for the O=E ratio.…”
Section: Data and Statistical Analysismentioning
confidence: 99%
“…Children with diseases such as congenital heart defect and hypothyroidism were also included. Other medical conditions were recorded as far as possible 25. The attending paediatricians were requested to review the paper records of the DS subjects and consider if the underlying medical conditions would affect significantly the physical growth and to indicate on the case record form in each case.…”
Section: Methodsmentioning
confidence: 99%
“…Common vision disorders found in DS patients include cataract, refractive error, squint, nystagmus, amblyopia and blepharitis 4. A North American study in the 1990s has found that cataracts, recurrent keratitis and keratoconus were the main causes for vision impairment in North American adults with DS 5.…”
Section: Introductionmentioning
confidence: 99%